2002
DOI: 10.1016/s0886-3350(02)01504-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Orbscan II slit-scanning elevation topography

Abstract: Orbscan II anterior surface elevation measurements differed significantly from Form Talysurf Analysis of complex test surfaces. However, the magnitude of the errors in the measurement of standard test objects was small, less than 0.20 microm centrally and 0.70 microm peripherally. Clinically, if similar accuracy of measurement is confirmed in the human eye, anterior surface elevation maps can be considered accurate representations of corneal shape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…In addition, several articles report that data displayed on the Orbscan may not be accurate. 10,11 The limitation of our study is that we have not validated this hypothesis using other devices. We will continue to evaluate the issue by including other parameters, such as anterior chamber depth, axial length, and pachymetry and other devices.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, several articles report that data displayed on the Orbscan may not be accurate. 10,11 The limitation of our study is that we have not validated this hypothesis using other devices. We will continue to evaluate the issue by including other parameters, such as anterior chamber depth, axial length, and pachymetry and other devices.…”
Section: Discussionmentioning
confidence: 90%
“…We agree with earlier authors [4,8,11] that corneal haze results in underestimation of corneal thickness possibly related to the reduced transparency and disturbed light scatter. Supporting this theory, Cairns et al investigated the accuracy of Orbscan II with different materials, and found that the results were more accurate in a material that scattered light in all directions [2]. On the other hand, in a semitransparent material the light was not evenly scattered but transmitted to a certain extent.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with that in a recent paper by Wei et al 29 showing no correlation between maximum corneal keratometry, an important indicator of keratoconus, 30 and maximum posterior elevation. Although the accuracy of posterior cornea measurements with the Orbscan have been questioned, 20,31 Cairns et al 32 found that the Orbscan could provide clinically accurate anterior surface elevation maps through tests using poly(methyl methacrylate) shapes modeled after the normal cornea.…”
Section: Discussionmentioning
confidence: 99%